Barriers of Pre-Hospital Services in Road Traffic Injuries in Tehran: The Viewpoint of Service Providers - Shahrokh Alinia; Hamidreza Khankeh; Sadat Seyed Bagher Maddah; Reza Negarandeh (Shiraz University of Medical Sciences, 2015)
Abstract Background: Iran is one of the countries with considerable road traffic injuries. Pre-hospital interventions have an important role in preventing mortalities and disabilities caused by traffic accidents.The present study aimed to explore the barriers of pre-hospital care in traffic injuries in Tehran, Iran. Methods: A qualitative content analysis approach was conducted based on 21 semi-structured interviews with 18 participants. A purposeful sampling method was applied until reaching data saturation. Interviews were transcribed verbatim, and then data condensing, labeling, coding and defining categories were performed by qualitative content analysis. Results: Four main barriers including 4 main categories and 13 subcategories emerged; they included Barriers related to people, Barriers related to metropolitan infrastructure,Barriers related to the profession and Barriers related to managerial issues. Conclusion: Based on the findings of this study, pre-hospital service barriers in traffic accidents have many dimensions including cultural, structural and managerial domains. Policy makers in health system can use these findings to promote the quality of pre-hospital services, especially in the field of traffic injuries.